Metal Exposure and SNCA rs356219 Polymorphism Associated With Parkinson Disease and Parkinsonism - Lucchini, Roberto G.; Guazzetti, Stefano; Renzetti, Stefano; Broberg, Karin; Caci, Margherita; Covolo, Loredana; Crippa, Patrizia; Gelatti, Umberto; Hashim, Dana; Oppini, Manuela; Pepe, Fulvio; Pilotto, Andrea; et al. (Frontiers in Neurology, 2020)
Objective: In the province of Brescia, Italy, historical neurotoxic metal exposure has occurred for several decades. This study aimed to explore the role of metal exposure and genetics on Parkinson’s Disease (PD). Methods: Cases were enrolled from four local clinics for movement disorders. Randomly selected controls non-affected by neurological or psychiatric conditions were enrolled from the same health centers. Data on sociodemographic variables, clinical onset and life habits were collected besides accurate occupational and residential history. Blood samples were collected from all participants for genotyping of target polymorphisms in genes linked to PD and/or metal transport. Results: A total number of 432 cases and 444 controls were enrolled in the study, with average age of 71 years (72.2 for cases and 70 for controls). The average age at diagnosis was 65.9 years (SD 9.9). Among the putative risk factors, family history of PD or Parkinsonism showed the strongest association with the diseases (OR=4.2, 95% CI 2.3, 7.6 on PD; OR=4.3, 95% CI 1.9, 9.5 for Parkinsonism), followed by polymorphism rs356219 in the alpha-synuclein (SNCA) gene (OR=2.03, 95% CI 1.3, 3.3 for CC Vs TT on PD; OR=2.5, 95% CI 1.1, 5.3 for CC Vs TT on Parkinsonism), exposure to metals (OR=2.4;, 95% CI 1.3, 4.2 on PD), being born in a farm (OR=1.8; 95% CI 1.1, 2.8 on PD; OR=2.6; 95% CI 1.4, 4.9 on Parkinsonism) and being born in the province of Brescia (OR=1.7; 95% CI 1.0, 2.9 on PD). Marginal OR of having PD depending by SNCA polymorphism and metal exposure highlights higher risk of PD among CC SNCA carriers and being exposed to metals. However, the interaction term was not statistically significant. Conclusions: Lack of evidence of statistical interaction between environmental and genetic factors may be due to the low frequencies of subjects exposed to metals and in each polymorphism variant and does not rule out biological interaction. Lifetime exposure to metals and genetic variation in SNCA gene are relevant determinants of PD and Parkinsonism in the highly industrialized area of Brescia, Italy.